2015
DOI: 10.1016/j.jcrs.2014.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Posterior chamber collagen copolymer phakic intraocular lens with a central hole to correct myopia: One-year follow-up

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
51
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 29 publications
13
51
2
Order By: Relevance
“…The postoperative UCVA and BCVA were −0.03 ± 0.08 LogMAR and −0.03 ± 0.07 LogMAR, respectively. The efficacy index and safety index were 1.27 and 1.28, respectively, which were consistent with previous studies [9, 1214]. These findings suggest that V4c-ICL is a safe and effective treatment for high myopia, and it significantly simplifies the ICL implantation procedure.…”
Section: Discussionsupporting
confidence: 91%
“…The postoperative UCVA and BCVA were −0.03 ± 0.08 LogMAR and −0.03 ± 0.07 LogMAR, respectively. The efficacy index and safety index were 1.27 and 1.28, respectively, which were consistent with previous studies [9, 1214]. These findings suggest that V4c-ICL is a safe and effective treatment for high myopia, and it significantly simplifies the ICL implantation procedure.…”
Section: Discussionsupporting
confidence: 91%
“…The ICL implantation with the standard method has proved to be an effective, safe, and predictable surgery for myopia correction [24,[28][29][30]. In our study, the LogMAR CDVA at 3 months after surgery was significantly improved with the safety index to be 1.18 in the OVD-free method group and 1.23 in the standard method group.…”
Section: Discussionmentioning
confidence: 47%
“…Alfonso et al [24] reported 8.5% endothelial cell loss 6 months postoperatively. Lisa et al [29] found a mean endothelial cell loss of 1.7% at 12 months postoperatively. In the OVD-free method group, a 4.6% endothelial cell loss at 3 months was comparable with the results from previous studies which used the standard method.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…At present, the ICL V4c decreases the rate of opacity and intraocular pressure increase without peripheral iridotomy because of the central hole design. Besides, pupil capture rarely occurs as the ICL haptics were placed in the ciliary sulcus [14,15].…”
Section: Discussionmentioning
confidence: 99%